PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH PT. BANK MANDIRI (PERSERO) Tbk. CABANG PEKANBARU TAMBUSAI - Fakhri, Rizqi (Eko dan Bisnis: Riau Economic and Business Review, 2021)
This study aims to determine the effect of service quality on customer satisfaction at PT. Bank Mandiri (Persero) Tbk. Pekanbaru branch of Tambusai. The total population is 99 people with a sample size of 99 respondents. Sampling in this study using a probability sampling technique. The research method used by researchers is descriptive quantitative, with simple linear regression data analysis techniques with SPSS 23 for windows as a tool. The results showed that there was an effect of service quality on customer satisfaction at PT. Bank Mandiri (Persero) Tbk. Pekanbaru branch of Tambusai. This can be seen from the acquisition of tcount>ttable (11,967> 1,988. This means that the Ho hypothesis is rejected and accepts Ha. Based on the simple linear regression equation Y = 5.016 + 0.668 X. Then seen from the constant of 5.016, while the quality of service (X) to satisfaction customer is proven positive b = 0.668 which means that each one-unit increase in service quality will be able to increase customer satisfaction PT. Bank Mandiri (Persero) Tbk. Pekanbaru branch Tambusai by 0.668 units From the results of R Square (coefficient of determination) of 0.596 or 59 , 6%. This shows that the quality of service to customer satisfaction PT. Bank Mandiri (Persero) Tbk. Pekanbaru branch Tambusai is 59.6% while the rest (100% - 59.6%) = 40.4% is influenced by other variables outside this research variable.